Compensatory renal hypertrophy and changes of renal function following nephrectomy - Sugaya, K (Hinyokika kiyo. Acta urologica Japonica, 2000)
We studied the changes in the serum creatinine level and the volume of the remaining kidney following nephrectomy using contrast-enhanced compounded tomogram (CT) scans. Twenty-five patients undergoing nephrectomy for renal cell carcinoma without obvious disease in the remaining kidney were carefully followed for a period of at least two years at our hospital. Twelve patients received follow-up CT scans each year after nephrectomy. The ellipsoid volume of the kidney was calculated by measuring the 3-dimensional size on CT scans. The mean relative volume (%) of the remaining kidney increased up to year 3 postoperatively, and the final mean relative volume at varying periods from years 2 to 7 was 120%. Kidneys that were smaller prior to nephrectomy showed a tendency to have a larger final relative volume after nephrectomy, although there was no significant correlation between the kidney volume prior to nephrectomy and at final measurement. The mean serum creatinine level was significantly increased at one year after nephrectomy, but it decreased significantly over time. Therefore, both compensatory renal hypertrophy and improved renal function seemed to be established within several years after nephrectomy. However, the improvement of serum creatinine was delayed compared with the increase of kidney volume. That is, renal plasma flow might be increased early by compensatory renal hypertrophy, followed within a few years by an increase in glomerular filtration and a decrease of serum creatinine